Nile Basin livestock water productivity - Peden, Donald G.; Alemayehu, M.; Amede, Tilahun; Awulachew, Seleshi Bekele; Faki, H.; Haileslassie, Amare; Herrero, Mario; Mapedza, Everisto D.; Mpairwe, D.R.; Musa, M.T.; Taddesse, G.; Breugel, P. van (CGIAR Challenge Program on Water and Food, 2009)
PN37 (Increasing Water-Use Efficiency for Food Production through Better Livestock Management - The Nile River Basin) set out to improve food security, reduce poverty and enhance agroecosystem health by managing livestock for more effective overall use of water. PN37 responded to water challenges posed by the CPWF, to the Nile Basin Initiative’s goal of better sharing benefits of water use, and to global need for the livestock sector to use agricultural water more efficiently and effectively. PN37 identified opportunities to increase livestock water productivity (LWP) in key production systems of Ethiopia, Sudan and Uganda. In all countries and systems, the research revealed important opportunities to increase LWP through site-specific sets of interventions including improved feed sourcing, enhanced animal production, water conservation, and strategic provisioning of drinking water. It concludes that better integration of livestock, crop, water, and land management can sustainably enhance livelihoods of many poor people throughout the Nile Basin and beyond that across much of sub-Saharan Africa.